Optimalisasi Bauran Pemasaran dan Konten Kreatif Wisata Selanjung Sungai Biuku Banjarmasin - Lalita Hanief; Noviana Sari; Syarief Hidayat (Jurnal Pengabdian ILUNG (Inovasi Lahan Basah Unggul), 2022)
Abstract  Biuku River or as we known Sungai Biuku was selected as 5 tourist villages in Banjarmasin out of 300 in Indonesia set by the Ministry of Tourism and Creative Economy (Kemenparekraf). The obstacles faced by Pokdarwis Senanjung in managing Biuku River tourism are the lack of promotion, floods that damaged facilities and the impact of the Covid-19 pandemic which had weakened tourism due to restrictions. The purpose of this community service activity is to optimize the economic potential of Selanjung Sungai Biuku Tourism through training in marketing communication mix and creative content. The community service method used is in the form of lectures, discussions, and tutorials. The Biuku River offers river tours, getting to know the biuku animal, getting to know traditional fishing tools, and enjoying the belaying plates typical of the Biuku River. The result of this activity is a cognitive change from Pokdarwis Senanjung regarding the 7P concept, public speaking that supports elements of people and creative content on social media. Members of Pokdarwis Senanjung can optimize the tourism potential of the Biuku River by applying the 7P concept. public speaking and active content in managing Instagram accounts to increase tourism promotion. Keywords: mix marketing, creative content, Sungai Biuku   Abstrak  Sungai Biuku terpilih sebagai 5 desa wisata di Banjarmasin dari 300 seIndonesia yang ditetapkan Kementerian Pariwisata dan Ekonomi Kreatif (Kemenparekraf). Kendala yang dihadapi Pokdarwis Senanjung dalam mengelola wisata Sungai Biuku yakni kurangnya promosi, bencana banjir yang merusak fasilitas dan juga dampak pandemi Covid-19 yang sempat melemahkan pariwisata karena adanya pembatasan. Kegiatan pengabdian masyarakat ini bertujuan mengoptimalkan potensi ekonomi yang dimiliki Wisata Selanjung Sungai Biuku melalui pelatihan bauran komunikasi pemasaran dan konten kreatif. Metode pengabdian pada masyarakat yang digunakan berupa ceramah, diskusi dan tutorial. Sungai Biuku menawarkan wisata susur sungai, mengenal hewan biuku, mengenal alat pancing tradisional, dan menikmati lempeng belaying khas Sungai Biuku. Hasil kegiatan ini yakni adanya perubahan kognitif dari Pokdarwis Senanjung mengenai konsep 7P, public speaking yang mendukung unsur people dan konten kreatif di media sosial. Anggota Pokdarwis Senanjung dapat mengoptimalkan potensi wisata Selanjung Sungai Biuku dengan menerapkan konsep 7P. public speaking dan konten keatif dalam mengelola akun instagram guna meningkatkan promosi wisata. Kata kunci: Bauran Pemasaran, Konten Kreatif, Sungai Biuku